Existence of Homoclinic Solutions for a Class of Nonlinear Difference Equations - Chen Peng; Tang XH (Advances in Difference Equations, 2010)
By using the critical point theory, we establish some existence criteria to guarantee that the nonlinear difference equation has at least one homoclinic solution, where , and is non periodic in . Our conditions on the nonlinear term are rather relaxed, and we generalize some existing results in the literature.